2011
DOI: 10.1118/1.3633941
|View full text |Cite
|
Sign up to set email alerts
|

A novel computer-aided lung nodule detection system for CT images

Abstract: A complete CAD system incorporating novel features is presented, and its performance with three separate classifiers is compared and analyzed. The overall performance of our CAD system equipped with any of the three classifiers is well with respect to other methods described in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(139 citation statements)
references
References 62 publications
2
132
0
5
Order By: Relevance
“…Other investigators have also presented similar results, such as, Riccardi et al [14] have recently presented a sensitivity of 71% with 6.5 FP/patient, and Tan et al [15] who reported 87.5% sensitivity at 4 FP detections per scan.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Other investigators have also presented similar results, such as, Riccardi et al [14] have recently presented a sensitivity of 71% with 6.5 FP/patient, and Tan et al [15] who reported 87.5% sensitivity at 4 FP detections per scan.…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that CAD for lung nodule detection could increase radiologists' performance [5][6][7] . Different approaches have been proposed for automatic detection of lung cancer on CT around the world: while some have evaluated different marketed CAD systems, other investigators proposed other methods and processing techniques [5][6][7][8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Dehmeshki et al [18] enhanced this method www.ijacsa.thesai.org by adding a shape-based methodology for nodule detection from spherical elements. Tan et al [19] utilized the three classifiers such as artificial neural network and genetic algorithm for lung nodule detection. To validate the proposed model, results were compared with SVM and fixed-topology neural networks based models.…”
Section: Introductionmentioning
confidence: 99%
“…The CAD system proposed by Tan et al [19] utilized three classier; two of them were artificial neural network and genetic algorithms and compared the results of these classifier with SVM and fixed-topology neural networks. Sua´ rez-Cuenca et al [20] have explored discriminant analysis (LDA), three types of support vector machines (SVM), artificial neural network (ANN) and quadratic discriminant analysis (QDA).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, systems for Computer-Aided Detection (CAD) have been gaining in popularity [1][2][3]. A significant focus on lung cancer is observed because it is by far the leading cause of cancer death among both men and women in the United States [4].…”
Section: Introductionmentioning
confidence: 99%